The use of vortex generators to improve the take-off and landing characteristics of transport category aircraft - V. G. Tsipenko; M. V. Sagaydak; V. I. Shevyakov (Научный вестник МГТУ ГА, 2022)
The issue of using vortex generators to improve the take-off and landing characteristics of a transport category aircraft has been considered. Three directions have been analyzed. The first: the installation of vortex generators on the nacelles of the main engines to increase the maximum value of the lift coefficient in landing modes. The second: the installation of vortex generators on the upper surface of the flap to increase the lifting characteristics of the wing by improving the flow around the flap. The third: the installation of vortex generators in the tail unit to increase the efficiency of control surfaces and reducing handling speeds. Examples of the use of vortex generators in each of the directions are given. It is shown that the improvement of the aerodynamic characteristics of the aircraft is possible in the presence of wing separation boundaries on the lifting surfaces in flight operating modes and the elimination of these zones by installing vortex generators. The results of computational studies, experiments in wind tunnels, as well as data from flight tests of an experimental aircraft confirming the effectiveness of using vortex generators are presented. The concept of increasing their stability by installing vortex generators in places with maximum flow velocity is proposed. Considering this concept, new locations for installing vortex generators on the upper surface of the flap, as well as on the fin of an experimental aircraft for repeated flight tests have been selected. The installation of vortex generators on the fin involves increasing the efficiency of the rudder to reduce the handling speeds. The possibilities of optimizing the parameters of the installation of vortex generators are considered. Recommendations are given on the choice of shape, size, and angles of their installation, depending on the tasks solved with the help of vortex generators and considering the possible increase in drag from their installation.